Decreased inpatient psychiatric admissions with telepsychiatry use during the COVID-19 pandemic - Lin, Brendon; Costakis, Anna; John, Majnu; Linder, Howard (Frontiers in Psychiatry, 2023)
Objective: This study examines the quality of care provided through telepsychiatry by comparing psychiatric hospitalization rates among patients receiving in-person psychiatric care prior to the COVID-19 pandemic with rates among patients receiving virtual psychiatric care during the COVID-19 pandemic. Methods: Mental health-related hospitalization rates among patients enrolled in a large academic hospital’s outpatient psychiatry programs between March 1, 2018 and February 28, 2022 were retrospectively analyzed. Four time periods were created, spanning March 1 to February 28 of the following year. Demographic and clinical data were collected from the electronic health record, and descriptive statistics were calculated. Change in hospitalization rate between time periods was evaluated using McNemar’s test. Results: In the 2018 time period, 7.38% of all enrolled patients were hospitalized, compared to 7.70% hospitalized in the 2019 period, 5.74% in the 2020 period, and 5.38% in the 2021 period. Patients enrolled in both the 2018 and the 2019 periods saw no difference in hospitalization rate between the two years (2.93% in 2018, 2.83% in 2019; p=0.830); patients enrolled in both 2019 and 2020 saw significantly lower hospitalization rates in 2020 (5.47% in 2019, 4.58% in 2020; p=0.022); and patients enrolled in both 2020 and 2021 saw no difference (3.34% in 2020, 3.23% in 2021; p=0.777). Conclusions: Psychiatric hospitalization rates significantly decreased between the 2019 and the 2020 periods, suggesting a decrease in admissions associated with adoption of telepsychiatry. Future research should differentiate the roles played by telepsychiatry and COVID-19-related factors in reducing hospitalization rates during the pandemic.